Handbook process and procedures for investment and construction by businesses in areas outside industrial parks in Bac Ninh province : (Lao động, 2010)
This handbook was developed as part of an investment climate advisory services project between IFC, a member of the World Bank Group, and Bac Ninh provincial people's committee. This technical cooperation initiative concentrates on strengthening inter-agency coordination and simplification of the administrative process and process and proceduces for investment and construction in areas out side industrial parks in Bac Ninh province.